Revisiting the Middle Baong Sand: Basin Floor Fan or Slope Fan in Origin? - Siti Nur'aini; Soejono Martodjojo; Frank W. Musgrove; Jon Bon (Berita Sedimentologi, 2001)
The Baong Formation contains three lithology units, namely shale unit (lower part), sand unit (middle part) and another shale unit (upper parts). The middle part of Baong Formation is usually called as the Middle Baong Sand (MBS) because it was deposited between two deep-marine shale lithologies during the Middle Miocene time. The Middle Baong Sand is the first turbidite reservoir found in Indonesia. Two feeder systems of Baong Sand came from the Barisan Mountain and the Malaka Shelf.Several authors had interpreted the Middle Baong Sand in Duyung Well as basin floor fan sediments. The Baong Sand in North Lho Sukon Deep was concluded to be slope fan complex, whereas in Jambuaye Utara Well was interpreted to be highstand sediments. The interpretation of this unit was merely leaned on log signatures or seismic characters without considering their presence on the regional geologic setting. The aim of this study is to investigate the depositional model of the Baong Sand within the geological setting of North Sumatra Basin.